2021
DOI: 10.1177/09596836211003220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on a subtropical montane peatland over the last two centuries: Evidence from diatom records

Abstract: Climate variability can induce rapid changes in peatland ecosystems, affecting both carbon cycling and vegetation succession. Diatoms are an important group of ubiquitous and diverse algae in peatlands. Until now, the responses of diatom communities to climate variability have rarely been explored in peatlands, especially in subtropical regions. In this study, monitoring and paleolimnological datasets were combined to decipher environmental changes of a subtropical montane peatland (central China) over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Electrical conductivity is a proxy for the total ionic concentration in natural waters (Rydin & Jeglum, 2013), and is often considered as the main factor responsible for diatom distribution in Sphagnum peatlands that are generally acidic and deficient in basic cations (e.g. Ca 2+ , Na + , K + and Mg 2+ ) (Chen et al, 2021; Fránková et al, 2009; Poulíčková et al, 2013). NH 4 + can be produced during microbial degradation of DOC and during grazing of bacteria by protozoa, and it is the key inorganic nutrient for diatom growth (cf.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Electrical conductivity is a proxy for the total ionic concentration in natural waters (Rydin & Jeglum, 2013), and is often considered as the main factor responsible for diatom distribution in Sphagnum peatlands that are generally acidic and deficient in basic cations (e.g. Ca 2+ , Na + , K + and Mg 2+ ) (Chen et al, 2021; Fránková et al, 2009; Poulíčková et al, 2013). NH 4 + can be produced during microbial degradation of DOC and during grazing of bacteria by protozoa, and it is the key inorganic nutrient for diatom growth (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the significant relationship between diatoms and altitude might represent potential effects of temperature (Gremmen et al, 2007). Previous studies have revealed that temperature is an important factor for the composition of moss‐inhabiting diatoms (Chen et al, 2021; Das et al, 2020; Gremmen et al, 2007). Nevertheless, the underlying relationship between diatoms and temperature is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations